Determination of brain injuries in dogs through computed tomography in Lima, Peru - Ojeda L., Claudia (2019)
The aim of this study was to determine encephalic lesions by computed tomography (CT scan) in 71 dogs that were submitted to the encephalic study by medical recommendation between 2011 and 2015 in Lima, Peru. The tomographic diagnoses were related to the sex, age, size and breed of the patients. Thirty-eight positive tomographic diagnoses of brain injury were identified (53.5%). The most frequent positive age group to brain injury was between 1 and 7 years and in medium-size dogs. The most frequent diagnosed lesions were ventricular dilation (29%, 11/38), brain neoformations (15.8%, 6/38) and hydrocephalus (15.8%, 6/38). Ventricular dilation occurred more frequently between 1 and 7 years and in Maltese and Poodle breeds, brain neoformations in dogs older than 7 years and in the Labrador breed, while hydrocephalus in dogs between 1 and 7 years old, mostly in Chihuahua and Pug.